THE METHODICAL ISSUES OF IMPROVEMENT OF ALREADY EXISTING TRAINING PROGRAMS IN SPHERE OF CIVIL BUILDING ENERGY EFFICIENCY ON THE BASE OF UKRAINIAN TRAINING CENTERS - Borychenkо, O. V.; Cherniavskyi, A. V. (Systems and Technologies, 2019)
This article presents the results of the proposal describing the conducting col-lection, reviewing and analysis of the information on existing trainings and training institutions for building energy efficiency in Ukraine. Also this article contents pre-liminary results of identification of capacity needs of training institutions for building energy efficiency for potential improvement of already existing training.There consider the following issues: 1) Short description of the methodical approach and proposing an outline of the study. 2) The main education and train-ing institutes for building energy efficiency in Ukraine. 3) Training and qualifica-tion measures on energy efficiency that are offered in Ukraine. 4) Identification of capacity needs of training institutions for building energy efficiency for potential improvement of already existing training.